Stochastic Modeling and Analysis with Energy Optimization for Wireless Sensor Networks. (12th May 2014) - Xu, DongHong; Wang, Ke
Due to the battery limitation of wireless sensor network (WSN), there is imperative requirement of energy saving and optimization in practical application of WSN. In order to optimize the energy of WSN, in this paper, a stochastic energy model for WSN is proposed. The model is based on the continuous time Markovian decision processes (CMDP) machine and spans both energy consumption and ensued transition costs. We use PRISM to analyze stochastic CMDP strategies of sensor devices as the formal framework. Simulation experiment is carried out to evaluate the model with given performance criteria. The result shows that the given model can effectively balance energy optimization and perform with high efficiency in WSN.